2021
DOI: 10.1038/s41438-021-00537-8
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis highlights contrasting levels of resistance of Vitis vinifera and Vitis amurensis to Botrytis cinerea

Abstract: Botrytis cinerea is a major grapevine (Vitis spp.) pathogen, but some genotypes differ in their degree of resistance. For example, the Vitis vinifera cultivar Red Globe (RG) is highly susceptible, but V. amurensis Rupr Shuangyou (SY) is highly resistant. Here, we used RNA sequencing analysis to characterize the transcriptome responses of these two genotypes to B. cinerea inoculation at an early infection stage. Approximately a quarter of the genes in RG presented significant changes in transcript levels during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 60 publications
1
19
0
Order By: Relevance
“…There are many V. vinifera cultivars and the cold hardiness of different varieties varies, with few V. vinifera varieties are suitable for cultivation in any specific country or region ( Zhan and Li, 2010 ; Wang et al., 2021b ). Most research on V. vinifera has focused on cultivation management ( Ju et al., 2019 ; Yue et al., 2020 ; Wang et al., 2021a ; Yue et al., 2021 ), fruit quality regulation ( Bohan et al., 2020 ; Li et al., 2021 ; Yang N. et al., 2021 ), wine-making characteristics ( Sun et al., 2021 ; Wei et al., 2022 ), grape and wine nutrition ( Cheng et al., 2021 ; Xu et al., 2021 ; Yang C. et al., 2021 ), and hardiness improvement ( Liu R. et al., 2021 ; Wan et al., 2021 ; Wang X. et al., 2021 ; Wang et al., 2021c ; Wang et al., 2022 ), but there has been little comprehensive work to determine the most appropriate methods for the evaluation of cold hardiness in V. vinifera . Most methods used thus far to investigate cold hardiness are relatively simple methods that are not targeted, so the results obtained using different cold hardiness evaluation methods will be different ( He, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are many V. vinifera cultivars and the cold hardiness of different varieties varies, with few V. vinifera varieties are suitable for cultivation in any specific country or region ( Zhan and Li, 2010 ; Wang et al., 2021b ). Most research on V. vinifera has focused on cultivation management ( Ju et al., 2019 ; Yue et al., 2020 ; Wang et al., 2021a ; Yue et al., 2021 ), fruit quality regulation ( Bohan et al., 2020 ; Li et al., 2021 ; Yang N. et al., 2021 ), wine-making characteristics ( Sun et al., 2021 ; Wei et al., 2022 ), grape and wine nutrition ( Cheng et al., 2021 ; Xu et al., 2021 ; Yang C. et al., 2021 ), and hardiness improvement ( Liu R. et al., 2021 ; Wan et al., 2021 ; Wang X. et al., 2021 ; Wang et al., 2021c ; Wang et al., 2022 ), but there has been little comprehensive work to determine the most appropriate methods for the evaluation of cold hardiness in V. vinifera . Most methods used thus far to investigate cold hardiness are relatively simple methods that are not targeted, so the results obtained using different cold hardiness evaluation methods will be different ( He, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…RNA-Seq transcriptome sequencing technology represents a comprehensive and accurate method for studying potential genes and gene regulatory networks mediated by plants response to abiotic stress [43]. Wan et al [44] determined the time of transcriptome sampling by observing the colonization of spores in leaves and analyzed the disease resistance in combination with the physiological changes of leaves during this time period. Considering the time specificity of transcriptome analysis, in this study, we used RNA-Seq sequencing technology, and selected selected the leaves without pathogen inoculation as the control group and the leaves on the 5th day after inoculation as the treatment group, in order to analyze the molecular mechanisms underlying the responses of two bluegrasses to powdery mildew infection at the physiological and transcriptomic levels and identify the metabolic pathways and genes associated with disease resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Referred to the method of Wan et al . [ 44 ], we combined the greater differences in the phenotypes and physiological indexes of two varieties to determine the time point for transcriptome analysis on the 5th day after inoculation, randomly collected 1.0 g leaves from the resistant variety ‘BlackJack’ and the susceptible variety ‘EverGlade’, and used the water treatment without inoculation treatment in the same period as the control, each variety was set with 3 biological replicates. They were labeled as ‘BlackJack’ control group (BCK), ‘BlackJack’ treatment group (BT), ‘EverGlade’ control group (ECK) and ‘EverGlade’ treatment group (ET).…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown that DEGs mainly play a role in perception, signal transduction, secondary metabolism, transcriptional regulation and plant–pathogen interactions (Gervasi et al 2018 ; Ma et al 2020 ; Wan et al 2021 ). Among the two genotypes of flax ( Linum usitatissimium L.), the upregulated genes in the resistant cultivar to Fusarium oxysporum were significantly higher than those in the susceptible cultivar (Dmitriev et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%